Naive Human Pluripotent Cells Feature a Methylation Landscape Devoid of Blastocyst or Germline Memory - Pastor, William A.; Chen, Di; Liu, Wanlu; Kim, Rachel; Sahakyan, Anna; Lukianchikov, Anastasia; Plath, Kathrin; Jacobsen, Steven E.; Clark, Amander T. (Cell stem cell, 2016)
Human embryonic stem cells (hESCs) typically exhibit “primed” pluripotency, analogous to stem cells derived from the mouse post-implantation epiblast. This has led to a search for growth conditions that support self-renewal of hESCs akin to hypomethylated naive epiblast cells in human pre-implantation embryos. We have discovered that reverting primed hESCs to a hypomethylated naive state or deriving a new hESC line under naive conditions results in the establishment of Stage Specific Embryonic Antigen 4 (SSEA4)-negative hESC lines with a transcriptional program resembling the human pre-implantation epiblast. In contrast, we discovered that the methylome of naive hESCs in vitro is distinct from that of the human epiblast in vivo with loss of DNA methylation at primary imprints and a lost “memory” of the methylation state of the human oocyte. This failure to recover the naive epiblast methylation landscape appears to be a consistent feature of self-renewing hypomethylated naive hESCs in vitro. [Display omitted] •Reversion or derivation of hESCs in 5iLAF results in SSEA4-negative cells•SSEA4-negative hESCs show gene expression consistent with naive pluripotency•Naive hESCs show lost “memory” of gamete and blastocyst methylation•Imprinting is lost in naive hESCs Pastor and colleagues show that reversion of primed hESCs in 5iLAF, or derivation of hESCs in 5iLAF, results in a population of naive cells characterized by loss of the marker SSEA4. However, these cells have a methylation pattern with little resemblance to blastocyst and near total loss of imprinting.